2012
DOI: 10.5487/tr.2012.28.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Ecological Protective Concentration using the Probabilistic Ecological Risk Assessment applicable for Korean Water Environment: (I) Cadmium

Abstract: Probabilistic ecological risk assessment (PERA) for deriving ecological protective concentration (EPC) was previously suggested in USA, Australia, New Zealand, Canada, and Netherland. This study suggested the EPC of cadmium (Cd) based on the PERA to be suitable to Korean aquatic ecosystem. First, we collected reliable ecotoxicity data from reliable data without restriction and reliable data with restrictions. Next, we sorted the ecotoxicity data based on the site-specific locations, exposure duration, and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… Sorensen et al (2007), Ra et al (2008), Nam et al (2012), Brock and Van Wijngaarden (2012) Example A (details in Supporting Information)…”
Section: Resultsmentioning
confidence: 99%
“… Sorensen et al (2007), Ra et al (2008), Nam et al (2012), Brock and Van Wijngaarden (2012) Example A (details in Supporting Information)…”
Section: Resultsmentioning
confidence: 99%
“…However, to protect environment there is a need to consider ecological risk assessment like the Netherlands and Canada. For Korean water environment management, EPC was derived by PERA [8,9], and in the case of soil environment, the study of EPC based on risk assessment was not attempted. Meanwhile, An et al [1] suggested ecological risk assessment methodology for soils in Korea by comparing methods of developed countries, such as the Nether-lands [2], Canada [7], and European Commission (EC) [10].…”
Section: Introductionmentioning
confidence: 99%